2016
DOI: 10.5527/wjn.v5.i3.233
|View full text |Cite
|
Sign up to set email alerts
|

Soy-based renoprotection

Abstract: Chronic kidney disease (CKD) is a significant public health problem as risk factors such as advanced age, obesity, hypertension and diabetes rise in the global population. Currently there are no effective pharmacologic treatments for this disease. The role of diet is important for slowing the progression of CKD and managing symptoms in later stages of renal insufficiency. While low protein diets are generally recommended, maintaining adequate levels of intake is critical for health. There is an increasing appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 182 publications
0
35
0
Order By: Relevance
“…The results of studies on the model of unilateral ureteral obstruction in rats receiving LPD demonstrated a decrease in the expression of the nuclear factor of Kappa B transcription (NFkB), the most important mediator of activation of many proinflammatory and profibrotic cytokines and TGF-β-key as a profibrotic factor in the renal tissue [28,30]. LPD with an addition of soy protein to the diet reduces tubulointerstitial fibrosis also due to suppression of tyrosine protein kinase as a powerful sclerosis stimulant [30].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of studies on the model of unilateral ureteral obstruction in rats receiving LPD demonstrated a decrease in the expression of the nuclear factor of Kappa B transcription (NFkB), the most important mediator of activation of many proinflammatory and profibrotic cytokines and TGF-β-key as a profibrotic factor in the renal tissue [28,30]. LPD with an addition of soy protein to the diet reduces tubulointerstitial fibrosis also due to suppression of tyrosine protein kinase as a powerful sclerosis stimulant [30].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…LPD with an addition of soy protein to the diet reduces tubulointerstitial fibrosis also due to suppression of tyrosine protein kinase as a powerful sclerosis stimulant [30]. Currently, the possibility of LPD influence to maintain the serum level of klotho protein, as an established strong early cardio and nephroprotective factor, is being actively studied [29].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 3 more Smart Citations